Revisiting the Use of Audiovisual Translation in Foreign Language Teaching - Betlem Soler Pardo (Quaderns)
For years, the translation method was disparaged in language teaching on the basis that it did not focus on communication. More recently, translation has made a return as scholars have come to realize how and why translation in the foreign language classroom might prepare students for the use of language in real communicative situations. The fact that translation and audiovisual translation (AVT) are now established disciplines with acknowledged linguistic benefits for language learning is both a cause and consequence of this paradigm shift. This article, first, begins with a revision of the different language teaching methodologies explored during the 20th century. We then proceed to focus on the different modalities of AVT and to present a critical analysis of best didactic practice in relation to this typology. Finally, it hones in on subtitling and dubbing, focusing on the variety of opportunities that both can offer in the field of language teaching.